2014
DOI: 10.1155/2014/359841
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Maprotiline in a Murine Model of Colitis in Normal and Reserpinised Depressed Rats

Abstract: Background. Anti-inflammatory and immunomodulatory activities have been reported for maprotiline, a strong norepinephrine reuptake inhibitor. In addition, some other antidepressant drugs have shown beneficial effects in experimental colitis. Methods. All the animals were divided into normal and depressed groups. In normal rats colitis was induced by instillation of 2 mL of 4% acetic acid and after 2 hours, maprotiline (10, 20, and 40 mg/kg, i.p.) was administered. In reserpinised depressed rats, depression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…[ 8 ] Furthermore, venlafaxine has shown to reduce inflammatory injury in animal model of induced ulcerative colitis. [ 18 ] In addition, anti-nociceptive and anti-inflammatory effects of venlafaxine were also noticed by Aricioğlu et al . in rat model of inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…[ 8 ] Furthermore, venlafaxine has shown to reduce inflammatory injury in animal model of induced ulcerative colitis. [ 18 ] In addition, anti-nociceptive and anti-inflammatory effects of venlafaxine were also noticed by Aricioğlu et al . in rat model of inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…These changes might be contribute to food intake and body weight dropping denoted in the present study. Abnormal integrity of intestinal wall in colitis consequently defected in the adsorptive function of the intestine leading to malabsorbance of protein and fats with anorexia (malnutrition of protein and fat) which caused decrease of protein and lipid synthesis in liver and weight loss during the first periods of experiment (Minaiyan et al, 2015). On the other hand, the effects of lactobacillus acidophilus on body weight and food intake was the subject of a difference between researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly administration of L. acidophilus to colitis rats was efficient to improve intestinal wall integrity and consequently improve structural and absorptive features of intestine and prevent diarrhea (Minaiyan et al, 2015). These benefit effects could be attributed to either of the potential mechanisms of L. acidophilus in maintaining the flora of the gut and ongoing carbohydrate fermentation; and/or by competitively inhibiting the growth of pathogens (Oelschlaeger, 2010;Ng et al, 2009).…”
Section: Total Serum Protein Albumin and Globulinmentioning
confidence: 99%
“…Our previous studies also demonstrated the anti-inflammatory activities of amitriptyline, fluvoxamine, maprotiline and venlafaxine (Hajhashemi et al, 2010[ 19 ], 2015[ 18 ]; Sadeghi et al, 2011[ 42 ], 2013[ 43 ]) and anti-colitis effects of maprotiline and fluvoxamine (Minaiyan et al, 2014[ 31 ], 2015[ 32 ]).…”
Section: Introductionmentioning
confidence: 88%